PEMANFAATAN THERMO ELECTRIC GENERATOR DARI KONVERSI ENERGI PANAS MENJADI LISTRIK UNTUK CHARGER PONSEL: Array - Silaban, Jisro; Nasution, Agus Almi; Roza, Indra (JiTEKH, 2020)
Thermo Electric generator element is a conversion system that converts heat into electricity by utilizing heat energy. This tool is designed which comes from wood fuel as a heat source, which can be converted by a Thermo Electric Generator (TEG) into electricity, because not all rural areas have electricity, so researchers use it as a back up for cellphone chargers. This research is a small scale only used for cellphone chargers, the results show that the temperature difference is a very influential factor in producing voltage output and electric current, the greater the temperature gradient (ΔT) produced, the greater the voltage output on the thermo electric. The working principle of the TEG element is that there is a temperature difference on each side, so the TEG will generate electricity. The TEG output is stabilized by an LM317 regulator to a constant 5V DC, the voltage does not fluctuate and does not cause damage to the cellphone. This element is packaged in the form of thin strips with two-sided cross sections, with one side absorbing heat and one side absorbing cold. The tool is designed to consist of 4 TEG with type TEG 12706 arranged in series to increase tension. The results of the research on the hot temperature side of at least 40.1 0C with a voltage of 0.70V DC and a maximum heat temperature of 187 0C with a voltage of 8.55V DC and on the cold side of a minimum of 0 0C a maximum of 26 0C with (P) power 0.105 W, (V) 8V DC voltage and (I) 0.013 mA current.